Modulation of surface phonon polaritons in MoO3 via dynamic doping of SiC substrate - Garcia-Pomar Juan Luis; Fandan Rajveer; Calle Fernando; Pedrós Jorge (Nanophotonics)
Polar biaxial crystals with extreme anisotropy hold promise for the spatial control and the manipulation of polaritons, as they can undergo topological transitions. However, taking advantage of these unique properties for nanophotonic devices requires to find mechanisms to modulate dynamically the material response. Here, we present a study on the propagation of surface phonon polaritons (SPhPs) in a photonic architecture based on a thin layer of α-MoO3 deposited on a semiconducting 4H-SiC substrate, whose carrier density can be tuned through photoinduction. By employing this system, we establish a comprehensive polaritonic platform where the propagation of the hybridized SPhPs can be manipulated dynamically due to their coupling with the electron plasma. Specifically, we demonstrate that increasing the doping of the 4H-SiC substrate allows for modulating the on/off switch behavior of SPhP propagation or its controlled canalization. Furthermore, this modulation leads to a notable increase in the Purcell factor, primarily attributed to the doping-induced flat dispersion curve creating ultra-slow light. These findings have significant implications for the development of nanophotonic and quantum technologies, as they enable the utilization of polaritonic materials exclusively.